How code-switching mediates politeness: Gender-related speech among London Greek-Cypriots - Gardner-Chloros, Penelope; Finnis, Katerina (Sociolinguistic Studies, 2003)
In this study we explore the three-way link between three topics which are usually studied independently in sociolinguistics, namely code-switching (CS), gender and politeness. Whilst steering clear of simplistic correlations between language and gender, we show how women in this community exploit CS in carrying out certain direct speech acts traditionally viewed as unfeminine. Conversational analysts often describe CS as a site for constructing meaning through juxtaposition, the direction of the switch being less important than the fact of the contrast. Nevertheless, an ethnographic study such as this shows the potential importance of associations between each language and relevant shared meanings. Switches into Greek are employed to evoke shared cultural connotations and by extension to create humour, to create a bond/show sympathy to the interlocutor, and to legitimize directness in giving orders or making requests, Greek being a language in which such directness is markedly greater than in English. Thus, through their use of CS, women in particular enact various politeness strategies, both positive and negative. This study confirms the value of studying both politeness and gender not only cross-culturally, but specifically in bi/plurilingual contexts, as a study of CS allows strategies and constraints which could pass unobserved in monolingual speech to be clearly highlighted.